THE IMPACT OF GLOBALIZATION ON ENGLISH LANGUAGE PEDAGOGY IN INDIA - Chandan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Globalization has transformed the educational landscape in India, significantly influencing English language teaching and learning. With the advent of economic liberalization in the 1990s and the surge in digital technology, the demand for English proficiency has skyrocketed, shaping pedagogical methodologies. This paper explores the dual impacts of globalization on English education, analysing its role in bridging and exacerbating the urban-rural divide. Specific attention is given to government initiatives such as the New Education Policy (NEP) 2020, which aims to modernize language education while ensuring inclusivity. This study employs a mixed-methods approach to assess the evolving trends in English language pedagogy, identifying key challenges and opportunities within diverse socio-economic contexts. It concludes with recommendations to enhance English education as a tool for empowerment in a globalized world.